2015
DOI: 10.15345/iojes.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ELT Students’ Academic (Language) Achievement: Language Learning Orientation and Autonomous Learning

Abstract: Learner autonomy is frequently debated among English language teachers and scholars around the world. From the perspective of Self-determination theory, autonomy supported learning environment has close relation with intrinsic motivation, higher perceived competence and academic achievement. The present study aims to define the prediction level of ELT students' academic achievement using their language learning orientation and autonomous learning. The participants of the study were the undergraduate students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Studies on learner autonomy have also attempted to find the interaction between LA and motivation (Bacquet, 2017;Gardner & Yung, 2015;Ma & Ma, 2012), LA and gender (Kırmızı & Kıraç, 2018;Koçak, 2003;Razeq, 2014), and LA and language proficiency (Jianfeng et al, 2018;Karatas et al, 2015;Mohamadpour, 2013). To extend the research on and gain further insights into the factors affecting LA, this study investigated the role of gender and major of study on students' perceptions of their readiness for autonomy.…”
Section: Research On Students' Readiness For La In Non-western Contextsmentioning
confidence: 99%
“…Studies on learner autonomy have also attempted to find the interaction between LA and motivation (Bacquet, 2017;Gardner & Yung, 2015;Ma & Ma, 2012), LA and gender (Kırmızı & Kıraç, 2018;Koçak, 2003;Razeq, 2014), and LA and language proficiency (Jianfeng et al, 2018;Karatas et al, 2015;Mohamadpour, 2013). To extend the research on and gain further insights into the factors affecting LA, this study investigated the role of gender and major of study on students' perceptions of their readiness for autonomy.…”
Section: Research On Students' Readiness For La In Non-western Contextsmentioning
confidence: 99%
“…Finally, Karatas et al. () found that an autonomous and supportive learning environment, paired with intrinsic motivation, predicted academic language achievement.…”
Section: Consequences and Determinants Of Self‐ And Identity‐related mentioning
confidence: 99%
“…It was also revealed that student participants are satisfied with the attitude of the instructor who pointed out their errors. It was also reported that the instructor pointing out errors helped students find their mistakes and become more autonomous (Karatas, Alci, Yurtseven & Yuksel, 2015). This also helped the instructor develop a more targeted instruction.…”
Section: Discussionmentioning
confidence: 96%